Professional development needs among school principals in the context of educational reform in Muscat, Oman / Saleh Said Hamad Al-Abri - Al-Abri, Saleh Said Hamad (2014)

(untitled)
The purpose of this study was to identify the core professional development needs of school principals in Muscat in the context of educational reform in Oman since 1998, when the general education curriculum was revamped to the basic education curriculum. The core professional development needs were initially identified and categorized into fifteen main areas and could be typified into two general types, that is, those concerning instructional matters (instructional leadership) and innovative initiatives (transformational leadership). This study also investigated challenges faced by school principals and their suggestions for improving school leadership and management in Muscat, Oman. The study largely used the survey method, which involved 80 school principals in the capital city of Muscat. As many as 25 principals from Cycle 1 and 55 principals from Cycle 2 participated in the study and they fully responded to the professional development needs survey questionnaire. Apart from the survey method, school visitations were made and some principals were interviewed to elicit information through face-to-face interactions regarding challenges, problems, and improvement efforts in school leadership and management related to school reform. Data obtained by survey was analyzed by descriptive statistics and inferential statistics using the SPSS software version 16. Descriptive statistics was used to assess principals’ perceptions regarding the extent of their professional development needs. Apart from that factorial analysis was used to examine the tenability of item groupings into their relevant factors, and to determine the dominant factors for professional development. Correlation matrix was also constructed to determine the inter-factor relational coherency. The results of the study showed that there were essentially fifteen areas or factors needed for professional development of school principals in the reform context. A majority of factors pertained to instructional matters, while other factors were concerned with leadership initiatives in making relevant changes suitable for new education policies and curriculum. Among the factors, building community involvement, leadership capacity, and problem solving were the dominant factors. Most principals contended that many professional development programs organized by the Ministry of Education did not match their professional development needs and roles. School principals were not properly trained in many aspects of school management and leadership. The implications of this study are: total retraining of school principals is needed whenever a system reform takes place, and new leadership competencies are needed to implement new policies and changes.